Acute Respiratory Deterioration Following Parvovirus B19 Infection in a Patient With Interstitial Lung Disease: A Case Report - Tomoki Kishaba; Satoshi Marumo; Yuya Nishida; Eri Nohara; Jukiya Higashi; Shohei Aoki; Chiaki Okura; Shiori Jinno; Noriyuki Tashima; Chie Morimoto; Takamasa Kitajima; Daiki Inoue (Respirology Case Reports, 2026)
ABSTRACT Acute exacerbation of interstitial lung disease (AE‐ILD) is often idiopathic, although viral infections are recognized precipitating factors. We report an adult patient with underlying ILD who developed acute respiratory deterioration in the setting of primary parvovirus B19 infection. A 70‐year‐old Japanese man was admitted to our department with a low‐grade fever and a facial rash. Two years prior to admission, the patient had been diagnosed with ILD, which had been treated with systemic corticosteroids that were subsequently discontinued following clinical improvement. High‐resolution computed tomography (HRCT) revealed newly developed bilateral ground‐glass opacities. Infection with parvovirus B19 was confirmed by serological testing and bronchoalveolar lavage results. Although the precise contribution of parvovirus B19‐associated lung injury, infection‐triggered AE‐ILD and acute exacerbation of the underlying ILD could not be definitively determined, steroid pulse therapy led to clinical and radiological improvement. This case highlights the importance of considering parvovirus B19 infection as a potential contributor to acute respiratory deterioration in patients with underlying ILD.